The effect of flame-retardant finish on jute and jute-cotton fabrics - Begum, Most Setara; Kader, Abdul; Milašius, Rimvydas (Wydawnictwo Politechniki Łódzkiej, 2022)
The ligno-cellulosic Jute fiber, which holds the second largest volume among the natural cellulosic fibers after Cotton. This study is focuses on the determination of flame-retardancy properties of pure Jute and Jute-Cotton fabrics treated with Pyrovatex CP New at various concentrations (50%, 60%, 70%, 80%, 90% owf, M:L: 1:10, 1:7, 1:5). A significant improvement in the flame-retardancy was determined on both fabrics. After ignition period, the recorded flame spread time was zero second on both FR treated fabrics; on the other hand, it was measured 21 seconds and 28 seconds to burn the entire length (15 cm) of untreated Jute and Jute-Cotton fabrics, respectively. Within these flame-spread times, the char length was 2.2 cm and 2.73 cm in Jute and Jute-Cotton fabrics, respectively. Tensile and tear strength also markedly decreased markedly after the FR finish in both warp and weft directions of both fabrics. The vertical flammability results reported in this study show the potential application of Pyrovatex CP New on Jute-based materials.
Keywords: jute; jute-cotton; flame-retardancy; flammability; char length; Pyrovatex CP New; juta; juta-bawełna; trudnopalność; palność; długość zwęglenia; Pyrovatex CP Nowość